A broadband 23.1 ∼ 27.2 GHz doherty power amplifier with peak output power of 24.3 dBm. Issue 1 (9th October 2019) - Fang, Yanfeng; Zhang, Yijiang
Abstract : Purpose: This paper aims to implement a new high output power fully integrated 23.1 to 27.2 GHz gallium arsenide heterojunction bipolar transistor power amplifier (PA) to meet the stringent linearity requirements of LTE systems. Design/methodology/approach: The direct input power dividing technique is used on the chip. Broadband input and output matching techniques are used for broadband Doherty operation. Findings: The PA achieves a small-signal gain of 22.8 dB at 25.1 GHz and a saturated output power of 24.3 dBm at 25.1 GHz with a maximum power added efficiency of 31.7%. The PA occupies 1.56 mm 2 (including pads) and consumes a maximum current of 79.91 mA from a 9 V supply. Originality/value: In this paper, the author proposed a novel direct input dividing technique with broadband matching circuits using a low Q output matching technique, and demonstrated a fully-integrated Doherty PA across frequencies of 23.1∼27.2 GHz for long term evolution-license auxiliary access (LTE-LAA) handset applications.